Kajian Perubahan Penggunaan Lahan di Kawasan Malioboro - Amelia da Conceicao da Costa; Willy Arafah; Herika Muhamad Taki; Sugihartoyo Sugihartoyo (Universitas Trisakti, 2021)
Yogyakarta city implies the city image and in the center of the city, is a tourist places. This is an increase in the number of tourists or demand accommodation, restaurant,the stores of all tourists needs.Thus, The goals of this research is to Identified the land use conversion in Malioboro Area by taking comparison in three years (2010, 2015, 2019) and to identified the factors that influence land use conversion in Malioboro Area. This research will use Spatial and Descriptive Statistics Methods to find out the scale of Land Use Conversion in three years (2010, 2015, 2019) and Factors that influence Land Use Conversion. The Result of this Research indicate the increase land use conversion from Residential Area to Commercial Area which in 2010 there is 140.60 Ha of Residential Zones however in 2019 there is a degradation of Residential Zones to 91.65 Ha, On the other side there is a improvement of Commercial Area which in 2010 there is 97.04 Ha of Commercial Area and in 2019 there is a 150.73 Ha of Commercial Area that exceed Regional Spatial Plan. Thus, there is a land use conversion in Malioboro Area which influence by demand of Amenities that cause by the increase of Tourist Visitation in Malioboro Area. The Land Use Conversion occur because of increase of quantity of Hotel and Amenities that cause demand of Amenities in Malioboro Areas. The conclusion of this research is Increase of demand for Tourist Visitation will increase the demand of space for commercial area, because there is an increase of Tourism Activities in Malioboro Area that influence Land Use Conversion in Research Area